Observatorium Gendoping: update 2005 - Gassmann, M.; Rusconi, S.; Flück, M. (2005)
The concept of the gene has been a main theme in modern biological thinking ever since the material origin of heritance has been investigated. This abstract principle states that phenotypic traits can be traced back to single, heritable elements. Thereby each cell would hold the molecular information for the making (i.e. expression) of the enzymes that carry out the different functions of living organisms. Historically, this view of the unitary origin of genetic transmission shares similarities with modern Olympic image of Sports as both have been introduced around the turn of the 19th century. Today the genetic paradigm has received a new dimension as the gene response is now known to underlie muscular adaptations to exercise training and presents a tempting menace for the sophisticated manipulation of athletic performance. The basic insight on the genetic underpinning of phenotypic potential dates back to the advent of molecular biology in the late sixties of the past century. Then, distinct elements in the form of nuclear DNA were identified to encode the single factors of cell function. Later biotechnological advancements allowed the isolation of genes and their cloning into host cells such as bacteria. Subsequent molecular biological innovations then led to the engineering and regulated production of active, recombinant proteins for therapeutic purposes in bacterial and eukaryotic cells. These later technological developments permit now to carry out targeted modifications of genes in the germline of small and large animal species. This produce transgenic animals with sometimes pronounced phenotypic "aberrations" which reflect all facets of living beings such as for example enhanced cell growth, and endurance or even death. Recently, gene transfer technologies have been expanded to somatic cells for the efficient introduction of genes in tissues of living animals via physico-electric methods or (viral) vehicles. As by today, some 660 somatic gene therapies have been initiated in the attempt to correct gene-based defects and diseases in humans. A variety of molecules was further tested in diverse animal models in the attempt to alter physiological functions and now enlarge the list of prospective gene-therapeutical targets in humans. To date, however, most of the early safety studies in humans have been halted due to the occasional appearance of severe effects. Only a few of these pilot studies are registered that have progressed to the phase III studies where larger cohorts of patients are followed up for clinical benefits of gene therapy.